Pengaruh Pengawasan dan Motivasi Terhadap Kinerja Karyawan Pada PT Promexx Stationery Kota Palembang - Wijaya, Richo; Halin, Hamid; Wulandari, Try (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Factors that can affect employee performance are supervision and motivation. This study aims to examine the effect of supervision and motivation on employee performance. This research begins with a survey of 60 employees as a sample of respondents at PT Promexx Stationery Palembang City. The type of data in this study uses primary data obtained directly by respondents using quantitative methods. Data collection techniques were carried out by distributing questionnaires to 60 respondents and conducting interviews. Based on the test results that supervision and motivation partially have a positive effect on employee performance (0.001 <0.05). And supervision and motivation simultaneously (sig F 0.001 < 0.05) have a positive effect on employee performance. So, it can be proven that supervision and work motivation are very important aspects in influencing the performance of employees of PT Promexx Stationery Palembang.